The Role of Broadband in Spurring Innovations in Kenya - Muchiri, Philip Rajab; Karume, Simon (Researchgate, 2016)
Objective: This study attempts to establish the role broadband plays in spurring innovations in Kenya. It discusses the importance of innovations in socio-economic development and the need for a regulatory framework to improve broadband infrastructure developments in Kenya. Background: In the last few years, Kenya has experienced an increase in the number of ICT enabled innovation hubs (Tech Hubs). Although they are few in number and generally not popular, there is great potential for broadband-based innovations in Kenya. The government has also invested heavily in broadband provision. Most of the innovations witnessed in Kenya are broadband enabled. There is need to provide policy, legal and regulatory environment to enable these innovations to flourish. The National Innovation System is the framework adopted for the study. Methodology: The study utilizes the dimensions of the Kenya National Innovation System as a basis of assessing the role of broadband in spurring innovation in Kenya. A descriptive quantitative study is adopted for this research. Data was collected from existing records, literature review and through interviews. Descriptive statistics were used to analyse the data. Results: There is a relationship between broadband diffusion and innovations development in Kenya. Broadband plays an important role in spurring innovations. Regulatory environment is vital in broadband infrastructure development in order to encourage innovations. Conclusion: The government should put in place policies and mechanisms to encourage innovations. Collaboration, investments in research and development should be encouraged between private and public institutions. A more detailed study on broadband enabled innovation is recommended for each sector of the economy.
Keywords: Broadband; Innovations; Policy; Innovation Hubs; Start-ups; National Innovation System (NIS)